METHODS OF MEASURING THE EFFECTS OF LIGHTNING BY SIMULATING ITS STRIKES WITH THE INTERVAL ASSESSMENT OF THE RESULTS OF MEASUREMENTS - P. V. Kriksin (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2017)
The article presents the results of the development of new methods aimed at more accurate interval estimate of the experimental values of voltages on grounding devices of substations and circuits in the control cables, that occur when lightning strikes to lightning rods; the abovementioned estimate made it possible to increase the accuracy of the results of the study of lightning noise by 28 %. A more accurate value of interval estimation were achieved by developing a measurement model that takes into account, along with the measured values, different measurement errors and includes the special processing of the measurement results. As a result, the interval of finding the true value of the sought voltage is determined with an accuracy of 95 %. The methods can be applied to the IK-1 and IKP-1 measurement complexes, consisting in the aperiodic pulse generator, the generator of high-frequency pulses and selective voltmeters, respectively. To evaluate the effectiveness of the developed methods series of experimental voltage assessments of grounding devices of ten active high-voltage substation have been fulfilled in accordance with the developed methods and traditional techniques. The evaluation results confirmed the possibility of finding the true values of voltage over a wide range, that ought to be considered in the process of technical diagnostics of lightning protection of substations when the analysis of the measurement results and the development of measures to reduce the effects of lightning are being fulfilled. Also, a comparative analysis of the results of measurements made in accordance with the developed methods and traditional techniques has demonstrated that the true value of the sought voltage may exceed the measured value at an average of 28 %, that ought to be considered in the further analysis of the parameters of lightning protection at the facility and in the development of corrective actions. The developed methods have been tested in surveys of the electromagnettic environment of 27 active high voltage electric substations with a 110 kV outdoor switchgear. The application of the techniques amended the accuracy of the information collected, the correctness of the evaluation of the electromagnetic environment of high-voltage substations with a 110 kV outdoor switchgear, the effectiveness of the developed adequate measures to protect against lightning effects.